Estilos e práticas parentais de mães adolescentes: um programa de intervenção - Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Altafim, Elisa Rachel Pisani; Schiavo, Rafaela de Almeida; Valle, Tânia Gracy Martins do (Moreira Jr. Editora, 2011)
The aim of this study was to describe the styles and parenting practices of adolescent mothers to evaluate the influence of participation in an intervention program of parental practices. 14 adolescent mothers contributed with this research. For the evaluation was used the Inventory of Parenting Styles of Babies Mothers (IEPMB). The results showed that the participants before beginning the group had an average of Parental Style Good, after participating in the group participants had an average of Parenting Style Great. The intervention group presented effectively promoting the acquisition and/or maintenance of positive parenting practices and the reduction in negative practices.

O objetivo deste trabalho foi descrever os estilos e práticas parentais de mães adolescentes, analisando a influência da participação num programa de intervenção de práticas parentais. Participaram desta pesquisa 14 mães adolescentes. Para a coleta de dados foi utilizado o Inventário de Estilos Parentais para Mães de Bebês (IEPMB). Os resultados demonstraram que as participantes antes de iniciarem o grupo apresentaram em média o Estilo Parental Bom, após a participação no grupo as participantes apresentaram em média o Estilo Parental Ótimo. O grupo de intervenção se apresentou de forma efetiva, promovendo a aquisição e/ou manutenção das práticas parentais positivas e a diminuição das práticas negativas.
Parenting style and parental practices of adolescents mothers: an intervention program
Keywords: Maternal behavior; Parental practices; Adolescent mother; Comportamento materno; Práticas parentais; Mãe adolescente